Relationship between HALP and PNI score with 1-month mortality after CABG - Koyuncu, Ilhan; Koyun, Emin (Frontiers in Nutrition, 2024)
Background: Coronary heart disease (CHD) is the most common cause of cardiovascular disease (CVD). CHD is among the most common causes of mortality and morbidity world wide. In addition, CHD is one of the most important causes of health expenditures world wide. Today, coronary artery bypass grafting (CABG) operations are a widely used surgical procedure and have an important place in the treatment of CHD. Many scoring systems have been evaluated to estimate the risk of mortality and morbidity. 30-day mortality rates after CABG have been reported as 1-4% in large-scale studies.Objectives: The aim of our study was to evaluate the relationship between 1-month mortality in patients undergoing CABG and the Hemoglobine, albumin, lymphocyte, platelet index (HALP score) and Prognostic nutritional index (PNI) calculated using laboratory data in the preoperative period.